Psychological factors implied in adherence to aerosol therapy in CF - Oteri, S.; Ullo, A.; Cristadoro, S.; Lombardo, M.; Magazzù, G. (Acta Biomedica Atenei Parmensis, 2014)
Introduction: Adherence to therapies in chronic diseases averages only 50%. Low adherence reduces the clinical outcomes of prescribed therapies. Discussion: In CF (Cystic Fibrosis) there is poor adherence for airway clearance and nutritional supplements due to lack of perceived efficacy and to the significant burden of daily routines and social/work activities. Conclusion: It is paramount to find new strategies to manage illness distress and to tailor, with together with caregivers and the patient, a better therapeutic approach.